2011
DOI: 10.1002/chem.201100388
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Ionic Liquid/ESI‐MS Methodology as an Efficient Tool for the Study of Transformations of Supported Organocatalysts: Deactivation Pathways of Jørgensen–Hayashi‐Type Catalysts in Asymmetric Michael Reactions

Abstract: The deactivation pathways of Jørgensen-Hayashi-type organocatalysts modified with an ionic liquid fragment in asymmetric Michael reactions of α,β-enals with C- (nitromethane, dimethylmalonate) or N-nucleophiles (N-carbobenzyloxyhydroxylamine) that involved an iminium-ion formation step were studied for the first time by the electrospray ionization mass spectrometry (ESI-MS). "Parasitic" side reactions and undesirable cation intermediates that poisoned the catalysts were identified in accordance with their m/z … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 136 publications
0
14
1
Order By: Relevance
“…More importantly, however, additional species that are not present in the unlabeled reference system have not been observed. There are no indications for an interference of the charge tag with the catalysis, in contrast to the findings with the flexible imidazolium-labeled proline derivatives reported previously [43]. …”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…More importantly, however, additional species that are not present in the unlabeled reference system have not been observed. There are no indications for an interference of the charge tag with the catalysis, in contrast to the findings with the flexible imidazolium-labeled proline derivatives reported previously [43]. …”
Section: Resultscontrasting
confidence: 99%
“…Few proline derivatives carrying a covalently fixed charge have been reported by now [43,53]. They consist of an imidazolium salt attached to hydroxyproline via an ester group at the end of a flexible alkyl spacer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 c While we were able to demonstrate that our fabrication method prevented catalyst deactivation between the Au/Pd NPs and the chiral organocatalyst to enable the asymmetric TOP, it was discovered that the chiral secondary amine catalyst was deactivated under aerobic conditions and that the heterogeneous catalyst could not be reused. Based on our preliminary experimental studies and related literature, 8 we concluded that the use of chiral heterogeneous secondary amines as organocatalysts for asymmetric TOPs was not a viable strategy due to the propensity of the covalent intermediates to undergo aerobic oxidation and become degraded. Therefore, we hypothesized that the use of chiral organocatalysts which activate the organic substrates through non-covalent interactions would lead to a more robust heterogeneous system that could be recovered and reused even under aerobic conditions.…”
Section: Introductionmentioning
confidence: 98%
“…While this phenomenon does not give a great effect in a single organocatalyzed reaction, it becomes crucial when the organocatalyst is repeatedly used after recycling. As shown by the same group oxidative poisoning of the ionic liquid tagged organocatalysts could be circumvented by working under oxygen free conditions (Maltsev, Chizhov et al 2011). It seems to be worthy to examine the applications of 1,2,3-triazolium-based ionic liquid tagged organocatalysts in organocatalyzed reaction running via intermediate enamines under oxygen free conditions because a better performance can be expected after recycling.…”
mentioning
confidence: 99%